2020
DOI: 10.1002/ange.202004311
|View full text |Cite
|
Sign up to set email alerts
|

Inverse Vulcanized Polymers with Shape Memory, Enhanced Mechanical Properties, and Vitrimer Behavior

Abstract: The invention of inverse vulcanization provides great opportunities for generating functional polymers directly from elemental sulfur, an industrial by‐product. However, unsatisfactory mechanical properties have limited the scope for wider applications of these exciting materials. Here, we report an effective synthesis method that significantly improves mechanical properties of sulfur‐polymers and allows control of performance. A linear pre‐polymer containing hydroxyl functional group was produced, which could… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 51 publications
0
13
0
1
Order By: Relevance
“…45 Thus, there is still a need to understand under what conditions the mechanism of the exchange reaction will play a key role to the function or properties of dynamic networks. The rekindled interest in these networks in the last decade has led to numerous articles on vitrimers for shape memory polymers, [35][36][37] shockwave dissipation, 38 flame retardants, 39 and solid electrolytes. 40 While initial work was focused on stress relaxation times and self-healing as a function of bond chemistry and polymer backbone, recent work has moved to investigating the effects of crosslink density, 41,42 defects 43 and solvent concentration 44 on the rheological properties of vitrimers.…”
Section: Introductionmentioning
confidence: 99%
“…45 Thus, there is still a need to understand under what conditions the mechanism of the exchange reaction will play a key role to the function or properties of dynamic networks. The rekindled interest in these networks in the last decade has led to numerous articles on vitrimers for shape memory polymers, [35][36][37] shockwave dissipation, 38 flame retardants, 39 and solid electrolytes. 40 While initial work was focused on stress relaxation times and self-healing as a function of bond chemistry and polymer backbone, recent work has moved to investigating the effects of crosslink density, 41,42 defects 43 and solvent concentration 44 on the rheological properties of vitrimers.…”
Section: Introductionmentioning
confidence: 99%
“…The Tg of a polymer is a key characteristic affecting properties such as mechanical strength and brittleness. 28 While it has been shown that the Tg of these polymers is variable owing to reasons such as difference in crosslinker identity and synthesis conditions, it is shown here that this polymer property is subject to aging over time.…”
mentioning
confidence: 66%
“…Typically, inverse vulcanized polymers are formed by reacting sulfur with a crosslinker or blending crosslinkers in one step, so fully cured polymers generally have relatively high strength, high Tg, and high solvent tolerance, but very low breaking strain (<15%) caused by their highly crosslinked structures. 11,13,20,[31][32][33][34][35][36][37] Conversely, not fully crosslinked polymers can be formed as stretchable material with low Tg, but all have very low strength (<2.0 MPa), and most of them are soluble in common solvents. 11,12,19,33,[38][39][40] This disadvantage of inverse vulcanized polymers limits their wider application in the areas that require the materials to have multiple tolerance to complex environments.…”
Section: Introductionmentioning
confidence: 99%
“…11,13,20,[31][32][33][34][35][36][37] Conversely, not fully crosslinked polymers can be formed as stretchable material with low Tg, but all have very low strength (<2.0 MPa), and most of them are soluble in common solvents. 11,12,19,33,[38][39][40] This disadvantage of inverse vulcanized polymers limits their wider application in the areas that require the materials to have multiple tolerance to complex environments. Hence, it's highly desirable to identify flexible crosslinked sulfur polymers with high strength, high strain, high toughness and great solvent tolerance to allow wider potential applications in practical environments.…”
Section: Introductionmentioning
confidence: 99%